Quinoline-para-quinones and metals: coordination-assisted formation of quinoline-ortho-quinones. Issue 8 (11th January 2018) - Kubanik, Mario; Lam, Nelson Y. S.; Holtkamp, Hannah U.; Söhnel, Tilo; Anderson, Robert F.; Jamieson, Stephen M. F.; Hartinger, Christian G.
Abstract : Attempts to obtain quinolinedione organometallics resulted in the metal-assisted formation of quinoline- ortho -quinones after reaction with protic solvents. Abstract : The reaction of the para -quinone 6, 7-dichloroquinoline-5, 8-dione with various transition metal dimers led to the unexpected formation of quinoline- ortho -quinone metal complexes. Systematic variation of the reaction conditions helped identify the solvent as the source of the carbonyl oxygen.